ANALISIS DETERMINAN EKSPOR PROVINSI SUMATERA UTARA: PENDEKATAN GRAVITY MODEL - Efori Telaumbanua (Universitas Negeri Medan, 2013)
Export Growth has been being one of important component in enhancing of economic growth of North Sumatera Province. During 2005-2010, the average growth of export rate of North Sumatera Province is 16,5 percent per year with 5,23 percent per year the average of it’s contribution to growth. The aim of this research is to detect the factors which affect the enhancement of export rate of North Sumatera Province during 2005-2010. With augmented gravity model approach, this research analyzes the effect of gross domestic product percapita rate and the population of each trading partner countries, geographical distance between North Sumatera Province and every trading partner countries, foreign direct investment and real effective exchange rate of North Sumatera Province, to the export rate of North Sumatera Province to every trading countries, such as United States of America, Netherland, China, India, Italy, Japan, Malaysia, Egypt, Singapore, and Ukraine. By using random effect model in pooled data processing, the result of this research describes that the gross domestic product percapita and the population of each trading partner countries affect positively and significantly to the export rate of North Sumatera Province. As well as foreign direct investment rate and real effective exchange rate of North Sumatera Province show the positive and significant effect. Whereas, geographical distance as the trade barrier, correlate negatively and significantly to the export rate of North Sumatera Province.